2017
DOI: 10.1155/2017/8235069
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effect of Fermented Papaya Extracts on Mammary Gland Hyperplasia Induced by Estrogen and Progestin in Female Rats

Abstract: Fermented papaya extracts (FPEs) are obtained by fermentation of papaya by Aspergillus oryzae and yeasts. In this study, we investigated the protective effects of FPEs on mammary gland hyperplasia induced by estrogen and progestogen. Rats were randomly divided into 6 groups, including a control group, an FPE-alone group, a model group, and three FPE treatment groups (each receiving 30, 15, or 5 ml/kg FPEs). Severe mammary gland hyperplasia was induced upon estradiol benzoate and progestin administration. FPEs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 44 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…This was reversed by metformin coadministration. Also, the EB-induced decrease in SOD and GSH-Px activities which could be as a result of accumulation of ROS (Peji et al 2003;You et al 2017) was significantly increased with metformin co-treatment. This probably suggests the antioxidant potential of metformin in EB-induced pathophysiological disorder in rats.…”
Section: Discussionmentioning
confidence: 98%
“…This was reversed by metformin coadministration. Also, the EB-induced decrease in SOD and GSH-Px activities which could be as a result of accumulation of ROS (Peji et al 2003;You et al 2017) was significantly increased with metformin co-treatment. This probably suggests the antioxidant potential of metformin in EB-induced pathophysiological disorder in rats.…”
Section: Discussionmentioning
confidence: 98%
“…Studies showed that HMG is related to endocrine disorders, the most of that are caused by the imbalance of estrogen and progestin. ( Liu et al, 2012 ; You et al, 2017 ) The treatment of HMG has become a heated topic in the world. HMG is mainly treated by surgery and medication ( Henry, 2014 ; Chen et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to reports in the literature, the MGH model was established by intramuscular injection of estrogen and progesterone (Wang et al, 2011; You et al, 2017). In this study, 16 female Sprague–Dawley rats were randomly divided into normal and model groups, with eight rats in each group.…”
Section: Methodsmentioning
confidence: 99%